2009
DOI: 10.1016/j.jnoncrysol.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modifier additions on the thermal properties, chemical durability, oxidation state and structure of iron phosphate glasses

Abstract: Modified iron phosphate glasses have been prepared with nominal molar compositions [(1−x)·(0.6P2O5-0.4Fe2O3)]·xRySO4, where x = 0-0.5 in increments of 0.1 and R = Li, Na, K, Mg, Ca, Ba, or Pb and y = 1 or 2. In most cases the vast majority or all of the sulfate volatalizes and quarternary P2O5-Fe2O3-FeO-RyOz glasses or partially crystalline materials are formed. Here we have characterized the structure, thermal properties, chemical durability and redox state of these materials. Raman spectroscopy indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
75
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(98 citation statements)
references
References 59 publications
14
75
0
5
Order By: Relevance
“…Microwave and conventional melting resulted in iron phosphate glasses with largely similar physical properties, although the microwaved samples retained slightly less phosphorus than the conventionally melted samples, which is consistent with other reported studies [31,32]. Due to the similar properties of the glasses prepared by the two methods, it is suggested that the Absorption (a.u) Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Microwave and conventional melting resulted in iron phosphate glasses with largely similar physical properties, although the microwaved samples retained slightly less phosphorus than the conventionally melted samples, which is consistent with other reported studies [31,32]. Due to the similar properties of the glasses prepared by the two methods, it is suggested that the Absorption (a.u) Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The good leaching durability is primarily caused by the presence of strong, hydration-resistant Fe-O-P bonds in these glasses [10,29]. Although the release of the alkali metal cations was highest for the IP glasses, their networks remain largely insensitive to the addition of cations and can solubilize them in high quantity without sacrificing leaching resistance, which is also consistent with that reported by Bingham et al [19].…”
Section: Leaching Resistancesupporting
confidence: 89%
“…The peaks in the spectra can be assigned to their vibrational mode according to known frequencies from IP glasses reported in Refs. [18][19][20], and NaAlP glasses in Refs. [21][22][23], some of which are summarized in Table 4.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Of more technological interest is the development of ternary systems such as the Na 2 O−CaO−P 2 O 5 system, which has been investigated extensively [12,38,39], and also the Na 2 O-Fe 2 O 3 -P 2 O 5 system [40], an extension of the developmental work on the binary Fe 2 O 3 -P 2 O 5 system [41] as a possible system for the encapsulation of nuclear waste.…”
Section: Phosphate-based Glass Structurementioning
confidence: 99%